Komunikasi Dakwah Habib Husein Ja’far Al-Hadar terhadap Generasi-Z - Maharani, Diandra Shafira; Nurfadilah, Adinda Alifya; Nasichah, Nasichah (CV. ITTC INDONESIA, 2023)
This paper examines the da'wah communication carried out by Habib Husein Ja'far Al -Haddar to gen-Z. Communication is an ability and skill that must be possessed by someone, especially preachers. Communication must be owned by a da'i, so that the effectiveness of the communication delivered occurs. So that the target audience can capture and receive the message that has been conveyed properly. This study aims to find out whether the da'wah communication carried out by Habib Husein Ja'far Al -Haddar to the Z-generation is good or not. The subject of this research is the Z-generation. This study uses a quantitative descriptive approach method. Data collection was carried out by distributing questionnaires to Z-generation which has an age range of 17-25 years as many as 50 respondents. The results of this study show significant results from the data we obtained.